The Dynamics of Risalah Nur Da’wa: An Analytical Study of Dershane Akhwat Jakarta - Salwa Haliza Asshiddiqi; Alivia Bunga Cahyani (al-Afkar, Journal For Islamic Studies, 2025)
The dynamics of da’wa in Indonesia face significant challenges, particularly in aligning traditional methods with the complexities of modern urban society. Traditional approaches, often limited to sermons and religious broadcasting, are considered less effective in addressing the evolving needs of urban communities. Dershane Akhwat Jakarta, a community-based on the teachings of Risalah Nur by Badiuzzaman Said Nursi, offers a contextual and inclusive da’wa model. This study examines the strategies employed by Dershane Akhwat Jakarta, particularly its interactive discussions, text readings, and open dialogues tailored to urban societal needs. The findings reveal that Dershane’s success lies not solely in transferring religious knowledge but in its flexibility to adapt to the participants' spiritual and social needs. This research confirms the validity of moderate da’wa approaches while expanding on their application by emphasizing the importance of social interaction and community engagement. Furthermore, integrating digital technologies emerges as a crucial innovation to engage younger, tech-savvy audiences. This study underscores the positive impact of Dershane’s inclusive methods in enhancing participants' understanding and strengthening community bonds. It advocates for strengthening the Dershane network nationally and internationally and advancing digital innovations to ensure the widespread and sustainable dissemination of Risalah Nur's values.